Aloe Vera Extract 75% Effective in Providing Xerosis Repair In Chronic Kidney Failure Patient’s - Rini Handriani; Wiwik Agustina (STIKes Patria Husada Blitar, 2020)
The prevalence of chronic kidney disease in Indonesia isÂ increasing, especially in Saiful Anwar Hospital Malang, because the patients must undergo hemodyalisis therapy. Hemodialysis therapy has an effect to induce xerosis. Untreated xerosis will cause pruritus. Therefore this condition needs to use moisturizer to prevent pruritus like aloe vera extract. The purpose of this research was to determine the effect of using aloe vera extract on the treatment of the skin of patients with chronic kidney failure. The research method was true experimental research and used simple random sampling technique to recruit 25 respondents. Aloe vera extract was used by rubbing it onto the skin with xerosis and assessment was conducted in the first, second and third week. The analysis of this research used the Kruskal-Wallis test and Linear Regression. The result of different test was p = 0.001 or Î± <0.01 showed that there was significant differences between groups of independent variables. The R ^ 2 value was 69% , it mean that aloe vera extract had an effect as much as 69% of improvement in skin conditions of xerosis patients and 31 % was influenced by other factors besides extract aloe vera. The results showed that aloe vera extract with 75% concentration gave the most effective treatment for xerosis patients. Therefore, aloe vera could be a therapy for xerosis as a management of independent nursing care with nursing problems of skin integrity disorders.